2002
DOI: 10.1007/s00415-002-0774-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic corticosteroid administration causes mitochondrial dysfunction in skeletal muscle

Abstract: Corticosteroid myopathy is a major clinical problem in patients undergoing chronic corticosteroid treatment and shows insidious and progressive muscle atrophy in proximal limbs. Although several mechanisms underlying the pathophysiology of muscle injury have been postulated, precise pathogenesis is still not clear. We evaluated the mitochondrial functions in patients receiving corticosteroids compared with those in healthy controls or patients not receiving corticosteroids. The serum levels and total productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 28 publications
3
64
0
Order By: Relevance
“…For transplantation patients, it is believed that the use of corticosteroid immunosuppressant therapy impedes the recovery of muscle fibers after kidney transplantation by causing a decrease in muscle protein synthesis and impairment of oxidative metabolism [18][19][20] . Other factors such as the age of the population, sedentary lifestyle and lack of systematic rehabilitation programs for kidney transplantation patients in Brazil, may lead these individuals to maintain deficits that may have negative influences on their functional outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For transplantation patients, it is believed that the use of corticosteroid immunosuppressant therapy impedes the recovery of muscle fibers after kidney transplantation by causing a decrease in muscle protein synthesis and impairment of oxidative metabolism [18][19][20] . Other factors such as the age of the population, sedentary lifestyle and lack of systematic rehabilitation programs for kidney transplantation patients in Brazil, may lead these individuals to maintain deficits that may have negative influences on their functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These changes can be partially attributed to immunosuppressive therapy, which commonly uses corticosteroids. This medication is associated with decreased synthesis and increased protein catabolism, which could hamper full return of the functions of kidney transplant patients [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the information available helped us to limit such a control treatment as much as possible, in agreement with ethical laws. In fact, systemic use of steroids is known to produce severe myopathy, which implies a possible risk of misinterpretation of their therapeutic potential if used as control treatment in healthy subjects (Mitsui et al, 2002). Previous experiments performed in our laboratory have shown that taurine, either in vivo and in vitro, does not modify the electrical and contractile parameters of skeletal muscle, unless in the presence of a taurine deficiency (De Luca et al, 1996).…”
Section: Methodsmentioning
confidence: 96%
“…GCs can indirectly affect muscle physiology through downregulating gonadal function and reducing the expression of the androgen receptor in skeletal muscle (219). Other factors have also been thought to be implicated in GC-associated myopathy, such as the GC effects on potassium and phosphate levels and mitochondrial function (209,222). A recent study showed that mice lacking PAI1 are protected from GC-induced muscle atrophy (32).…”
Section: Muscle In Csmentioning
confidence: 99%